Prinsip Kepentingan Terbaik Bagi Anak Dalam Diversi Pada Sistem Peradilan Pidana Anak - Ni Ketut Wiratny (Universitas Mahendradatta, 2018)
Article 28 B Paragraph (2), the Constitution of the Republic of IndosesiaYear 1945 each child shall have the right to survival, grow and develop and shallbe entitled to protection of violence and discrimination, Protection of the rights ofthe child shall be contained in the UN Convention on the Rights 1989, has beenratified by more than 191 countries, including Indonesia as a member of the UNthrough Presidential Decree No. 36 of 1990. Thus the UN convention has becomeIndonesian law and binds all Indonesian citizens . To enforce the provisions setforth in the Convention on the Rights of the Child. as well as the basic principles ofthe Convention on the Rights of the Child include: a) discrimination of nonmembers,b) the best interests of the child; c) the right to life, survival anddevelopment; and d) an appreciation of the child's opinion. The best interest of thechild or in English is called the best interests of children is the basic principleunderlying the protection of the child. The best interests of the child should beviewed as 'paramount importance' or top priority. This principle is contained ininternational law and national law related to child protection. The child must beprotected, even if the child is a child in conflict with the law. The principle of thebest interests of the child as set forth in Point 14.2 of The Beijing Rules which statesthat